Kedudukan Ilmu Mantik Dalam Pemikiran Islam: The Position of Logic in Islamic Thought - Wahab, Muhammad Rashidi; Hamat, Mohd Fauzi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
Logic is a science of knowledge, tool or introductory medium that discusses methods on accuracy and systematic way of thinking. It is widely used in various fields of knowledge, including in Islamic studies. Nonetheless, there are disputes among the Muslim community regarding this subject derived from scholars’ disagreement between accepting and rejecting it. This polemic has created a state of disharmony within the circle of discussion through the efforts of defending their judgments. Through the content analysis method, this article examines the attitude of the scholars of Ahl al-Sunnah wa al-Jama‘ah towards the science of logic. This article also studies the influence of logic in Islamic discourse to get a comprehensive overview. This study shows that logic holds an important position in Islamic thoughts considering that it is utilized to defend Islam and to strengthen the beliefs. Thus, scholarly judgments that uphold the study of logic as a must and required are considered more accurate and also compatible with current demand.